Role of Community Participation with Respect to New Health Promotion - Sukmee, Rattawut (Journal of Health Science of Thailand, 2017)
Towards the goal for healthy people and healthy community, this research was aimed at studing the role of community participation on health promotion with the new approach. The research applied both qualitative and quantitative methods. For quantitative part, structured questionnaire was applied with 450 leaders and core persons in the community and officials from health and non health sectors who were involved in health promotion work. While in a qualitative part, in depth interview with the structured guideline was applied with 86 health workers and partners who worked on health promotion at sub-district, district and provincial level in Chiang Mai province. This research was conducted during January-July 2007. Descriptive analysis, percentage, means, and standard deviation was used as a statistical method for data analysis. For triangulation, content analysis was used to analyze information obtained from in-depth interview. Of the total 450 persons who were interviewed with the structured questionnaire, most of the respondents were female (57.6%) aged 20-29 years (29.8%), married (53.6%), laborer/employee (30%) and primary school graduates (28.4%). It was found that in term of attitude towards promoting healthy behavior through personal hygiene care, they strongly agreed with taking shower at least one time/day (91.9%), hand washing before meal and after using tarlets, (86.9%), vegetable or fruit intake (70.4%), agreed not to avoiding food with preservatives (53.5%). For healthy behavior through exercise, 44.7 percent of respondents strongly agreed with exercising by doing housework and toiling and 32.7 percent agreed that one should do exercise at least 3 times a week, starting from warm up, peak and cool down before finish an exercise. For the role of community participation on health promotion, 52.5 percent strongly agreed not to invade and deteriorate environment, in stead community participation in preserving public forestry area should be promoted; 38.9 percent strongly endorsed community participation and joining with village meeting if there is an opportunity. And 31.2 percent strongly agreed with promoting free pollution in the community. Finding from in-depth interview also revealed that defining vision and mission of the provincial health office (PHO) emphasizing on community participation is necessary. Additionally most of key persons interviewed from both health staffs and partners suggested that it was also important that the provincial health office would move proactively on health promotion work. It is also expected that the PHOีs role would cover i) supporting role, ii) directing role, iii) evaluator, and iv) implementer. In conclusion, the role of health promotion with the new approach that contributing to healthy people is very simple. It can be done through awareness raising with people and community and become part of their routine. Partnership among all involved is a key for success.